Development of Multimedia Google sites for Ehancing Conceptual Understanding and Students Motivation in Digestive System Topic - Wardatul Hakimah; Dian Nugraheni; Habiddin; Yayuk Mulyati; Erti Hamimi (JIPI (Jurnal IPA & Pembelajaran IPA), 2025)
This research is based on the limited use of learning media which results in students experiencing difficulties in understanding lessons and a lack of learning motivation, which impacts low learning outcomes. This research aims to develop valid, effective, and practical google sites multimedia to improve conceptual understanding and student motivation in the material of the digestive system. The research method used was research and development (R&D) with the ADDIE model, namely: analyze, design, development, implementation, evaluation. Data were collected through observation, interviews, and questionnaires. Validation by material experts showed a "very valid" category with a percentage of 87.74%, while media experts reached 90.22%. The effectiveness test produced a significance of 0.000 (<0.05), indicating a significant difference between the pretest (63.28) and posttest (89.62) scores, with an average increase in N-Gain of 0.72 (high). The learning motivation questionnaire obtained a score of 88.77% (very high). The practicality test by teachers produced 99.10% and and user responses from students 92.07%, indicating this application is very practical. The research results prove that google sites is feasible, effective, and practical to use to improve students' conceptual understanding and motivation in the digestive system topic.